Solid phase gastric emptying times in the dog measured by 13C-sodium-acetate breath test and 99mTechnetium radioscintigraphy - Schmitz, S.; Failing, K.; Neiger, R. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2010)
Objective: The aim of the study was to assess solid gastric emptying via non-invasive 13C-sodium acetate breath test and compare this technique to 99mTechnetium scintigraphy in 12 healthy adult dogs. Material and methods: The dogs were fed a test meal containing either 100 mg 13C-sodium acetate or 150–250 MBq 99mTechnetium albumin colloid. Breath test and scintigraphy were performed on two consecutive days; this set of procedures was repeated in all dogs. Breath samples and scintigrams were obtained at baseline and every 15 minutes for 4 hours, then every 30 minutes for another 2 hours. 25%, 50% and 75% gastric emptying times for breath test (Gt25%b, Gt50%b, Gt75%b) and scintigraphy (Gt25%s, Gt50%s, Gt75%s) were calculated and compared. Results: The mean (± SD) Gt50%b and Gt50%s were 165 (± 28.1) and 71 (± 16.6) minutes, respectively. There was a significant correlation at all three gastric emptying times between breath test and scintigraphy. Conclusion and clinical significance: While gastric emptying times between both methods varied considerably, both methods correlated significantly showing that the gastric emptying breath test can be used to assess gastric emptying times in dogs.
Keywords: Isotope; motility; region of interest; stomach; technetium